Seasonal Variations Of Attached Cyanophyceae Algae on Cocreate Brideges In Tigress Rivere From Baghdad - Al Magdamy, Buthaina Abdul Aziz Hassan; Zainab Faleeh Moussa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The attached Cyanophyta community is a model for monitoring aquatic systems and interpreting environmental change in aquatic systems. The present study aims to conduct a seasonal study on Cyanophyta attached to the concrete abutments of three bridges (Al-Jadriya Bridge, Bab Al-Moadam Bridge, and Al-Muthanna Bridge) in the Tigris River within the city of Baghdad, central Iraq (from October 2021 to June 2022). The study included the quality of Cyanophyta and, the eleven environmental parameters (water temperature, electric conductivity, salinity, pH, total alkalinity, Calcium, Magnesium, dissolved oxygen, total dissolved solids, total phosphorus, and total nitrogen). Monthly samples were taken from the water under each bridge from three sampling sites in the river, and the results were presented as four seasons. A total of 45 Cyanophyta taxa were identified in the three orders. Order: Chroococcales 11%; Order: Oscillatoriales 64%; Order: Nostocales 25% dominance of Oscillatoriales from the second site, and the highest number of species recorded in the autumn. The study showed clear differences in the total number of algal species attached to different sites. The study was able to add a new record species to the Iraqi algae flora, which is Lyngbya sordida Gomont.